Utilization Rate of Natural Family Planning and its Related Factors - M Ahmad Shirvani; A Omidian (Tehran University of Medical Sciences, 2007)
Background & Aim: Although natural contraceptive methods have been used for centuries, they have high failure rates so family planning programs tend to promote modern methods. Knowing utilization rate of natural methods and its pattern could help the planners to design effective family planning programs. This study was designed to identify the utilization rate of natural family planning and its related factors in Ghaemshahr, Iran, 2005Methods & Materials: In this cross-sectional study, 304 married and non-pregnant women aged 15-49 years that were not intended to become pregnant were recruited using systematic random sampling. All participants completed the informed consent form. Data were collected using a content valid and reliable (r=0.84) questionnaire. Data were analyzed using descriptive statistics, Chi-square, ANOVA and t-test.Results: The utilization rate of natural and medical methods were 39.5% and 60.5%, respectively. Among all various methods, withdrawal was the most prevalent one (37.5%). The frequency of breastfeeding and safe period were 1% and 0.3%, respectively. The most cited reasons for using natural methods were fear of side effects of other methods (50.6%), its convenience (36.5%), preference of spouses (32.6%), and the wrong perception of being as effective as other methods (22.5%). There were significant associations between age (P=0.003), marriage duration (P=0.01), number of children (P=0.0001) and living in urban area (P=0.0001) with utilization rate of natural methods. Health providers were reported to be the main source of information.Conclusion: Although family planning programs tend to promote modern methods, the wide spread use of natural methods especially withdrawal method suggests that those couples that are interested in continuing the method should be educated for correct use of it. On the other hand, it is recommended that family planning packages should contain programs to increase knowledge, to correct the wrong believes, to consult with couples, to targeted men and other groups of the populations and finally to activate mass media.